Effect of Dividend, Profitability, and Interest Rates on Firm Value with Leverage as Moderating - Sihombing, Pardomuan; Pranata, Natanael; Kwee, Yohanes (SAN Scientific, 2024)
This research aims to determine the effect of dividend policy, profitability, and interest rates on firm value with leverage as a moderating variable in coal sector firms listed on the Indonesia Stock Exchange. The sampling method uses purposive sampling, with several predetermined criteria, the number of samples is 12 coal sector firms. This research uses panel data analysis. The appropriate panel data model in research uses a fixed effects model. The research results show that dividend policy, profitability, and interest rates have no effect on firm value, and leverage as a moderating variable can strengthen the relationship between dividend policy and profitability on firm value. Companies that use leverage can improve firm performance so that firm value increases. Managerial implications stem from these findings. Executives should adopt dividend policies aligned with firm growth objectivesbalancing shareholder returns with reinvestment opportunities. Enhancing profitability through operational efficiency and strategic decision-making remains paramount. Additionally, monitoring interest rate fluctuations enables proactive management of financing costs and investment decisions. This study examines the influence of dividend policy, profitability, and interest rates on firm value, with leverage acting as a moderating variable. The findings provide valuable insights for managerial decision-making